Book Review: Data Rules: Reinventing the Market Economy by Cristina Alaimo and Jannis Kallinikos - Nicholls, Rob (Journal of Telecommunications and the Digital Economy, 2024)
Data Rules: Reinventing the Market Economy by Cristina Alaimo and Jannis Kallinikos offers an exploration of the societal, cultural, and epistemological dimensions of data, challenging conventional views of data as neutral or merely technical. By introducing original concepts such as ‘data rules’ and ‘data complementarities’, the authors provide a unique perspective on how data reshapes markets, social relationships, and innovation ecosystems. The book balances historical context, theoretical insight, and contemporary examples, making it a useful resource for interdisciplinary readers. The book leaves gaps in addressing actionable regulatory frameworks or the political dimensions of platform capitalism. The volume represents a useful ‘rounding out’ of the literature in this specialist field.